PENGARUH KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KARYAWAN PT. BINA VALASINDO DOLARASIA SEJAHTERA UTAMA JAKARTA - Meylani Tuti; Etty Nurwati; Anisa Nurul Karimah (Human Capital Development, 2020)
The purpose of this research is to analyze the effect of leadership and organizational commitment on performance through motivation. The population of this research are employees of PT. Binavalasindo Dolarasia Sejahtera Utama Jakarta. The sampling technique by saturation with 158 respondents. Method of collecting data by census technique using questionnaire that has been tested its validity and reliability. Data analysis by descriptive and quantitative. The quantitate analysis use Path Analysis with SPSS 20. The result of the research shows that Leadership has a significant effect towards Motivation by the value of 4.62, while Organizational Commitment has a significant effect towards Motivation by the value of 5.76, Leadership has a significant effect towards Performance by the value of 3.01, while Organizational Commitment has a significant effect towards Performance by the value of 2.93, Motivation has a significant effect towards Performance by the value of 8.57, Leadership has a significant indirect effect on Performance through Motivation by the value of 2.74, while Organizational Commitment has a significant indirect effect on Performance through Motivation by the value 4.43.